2017
DOI: 10.1891/0889-8391.31.3.158
|View full text |Cite
|
Sign up to set email alerts
|

Program ACTIVE: Cognitive Behavioral Therapy to Treat Depression in Adults With Type 2 Diabetes in Rural Appalachia

Abstract: High rates of type 2 diabetes (T2DM) and depression exist in rural Appalachia with limited access to psychotherapeutic treatment. No manualized cognitive behavioral therapy (CBT) treatment materials exist that are culturally tailored for individuals in this region with T2DM. We describe the development of the Program ACTIVE CBT intervention for use with adults with T2DM and depression by mental health providers in rural Appalachia. Qualitative and quantitative methods were used to test the feasibility and acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…While these studies highlight the importance of treating depression/psychological symptoms, it is also important to screen for these comorbidities. One study showed adults may not have received adequate treatment for depression, which in turn, may have affected the non‐pharmacologic and pharmacologic management of T2DM 59 . Additional studies are required to evaluate novel strategies to treat comorbidities and improve T2DM self‐management.…”
Section: Resultsmentioning
confidence: 99%
“…While these studies highlight the importance of treating depression/psychological symptoms, it is also important to screen for these comorbidities. One study showed adults may not have received adequate treatment for depression, which in turn, may have affected the non‐pharmacologic and pharmacologic management of T2DM 59 . Additional studies are required to evaluate novel strategies to treat comorbidities and improve T2DM self‐management.…”
Section: Resultsmentioning
confidence: 99%
“…Recent evidence from multiple clinical trials has demonstrated that the use of cognitive behavioral therapy (CBT) delivered through individual counseling or telephone-based therapy sessions is effective in improving depression outcomes. 21-24 A combination treatment of CBT counseling and antidepressant medications has shown effectiveness in depression outcomes. 25 The combination of CBT and community-based exercise interventions tailored for diabetes and delivered by community mental health and exercise professionals is the only modality that has shown effectiveness in improving both depression and A1C values.…”
Section: Psychosocial Considerations For People With Diabetesmentioning
confidence: 99%
“…Sixty-seven percent of participants completed the intervention, which is comparable to the 67% to 80% completion rates reported in other studies of CBT depression interventions for adults with T2DM. 27,28 The completion rate for the mental health co-component of the intervention was 13% lower than that for participants in the Boot Camp alone, which was 80% during the study period. This suggests that persons with T2DM who are also experiencing moderate depression and/or anxiety may find it more challenging to successfully complete self-care programs, possibly due to the impact of their mental health status.…”
Section: Discussionmentioning
confidence: 90%
“…24 Cognitive behavioral therapy (CBT) is one of the most widely studied interventions for depression and anxiety, generally, 21,25 and has also been shown to be effective in the treatment of comorbid depression and anxiety in T2DM patients. 26-28 CBT is a structured and time-limited psychotherapy that emphasizes the relationships among cognitions, behaviors, and emotions. 29,30 CBT includes behavioral activation, cognitive restructuring, problem-solving, and relapse prevention.…”
mentioning
confidence: 99%